Column Study and Desorption Performance of Coffee Biomass-Calcium-Alginate Beads to Remove Pb²⁺ Ions from Aqueous Solutions - Hanifah, Sarina; Rusnadi, Rusnadi; Stiawan, Elva; Widianti, Riskia Chandra (Program Studi Kimia Universitas Negeri Jakarta, 2025)
Heavy metal pollution, particularly by lead (Pb²⁺), poses a serious environmental threat and can significantly impact human health. This study aims to evaluate the performance of an adsorbent composed of a mixture of coffee waste and calcium alginate (Coffee-Calcium-Alginate/CCA beads) in removing Pb²⁺ ions through column experiments, as well as to assess the desorption efficiency and reusability of the adsorbent. Column studies were conducted at 1 ppm Pb2+ ions initial concentration, a flow rate of 2.2 mL/min, using a column with a length of 10 cm and a diameter of 7 mm to determine the breakthrough time of the adsorbate, while desorption was performed using HNO₃ to evaluate the efficiency of Pb²⁺ ions release and the potential for adsorbent reuse. The results demonstrated that the CCA adsorbent was able to retain high efficiency over two adsorption–desorption cycles, with desorption efficiencies of 96.35% and 86.64%. The desorption mechanism involves protonation of carboxylate groups and competition between H⁺ and Pb²⁺ ions at the active sites. Overall, CCA beads exhibit promising potential as an effective and reusable adsorbent for treating water contaminated with heavy metals. Future research could explore the effects of varying initial Pb²⁺ ions concentrations and column height to gain a more comprehensive understanding of desorption dynamics within the column system. Keywords: adsorption, coffee biomass, calcium alginate, Pb2+, leads